SURGICAL REPAIR OF RELAPSING SACRAL HERNIA AFTER PRESACRAL TUMOR RESECTION VIA POSTERIOR APPROACH (KRASKE PROCEDURE) - GALAMA, Rita (2023)
Presacral tumors are rare and mostly congenital. If, on the one hand, the Kraske procedure ensures complete excision, reducing local recurrence, on the other hand, it has the development of an incisional sacral hernia as a complication. We present a case of a 44-year-old woman with a relapsing sacral hernia after a posterior approach (Kraske procedure) for the resection of a presacral extra-ovarian fibroma. We describe a surgical repair with dual mesh via a posterior open approach. Twelve months after this surgical procedure, the patient shows no signs of recurrence. To the best of our knowledge, this is the first report, in the literature, on surgical correction of presacral hernia after a Kraske procedure.